2020
DOI: 10.1021/acs.cgd.9b01693
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid and Oligopeptide Effects on Calcium Carbonate Solutions

Abstract: Biological organisms display sophisticated control of nucleation and crystallization of minerals. In order to mimic living systems, deciphering the mechanisms by which organic molecules control the formation of mineral phases from solution is a key step. We have used computer simulations to investigate the effects of the amino acids arginine, aspartic acid, and glycine on species that form in solutions of calcium carbonate (CaCO3) at lower and higher levels of supersaturation. This provides net positive, negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 89 publications
0
23
0
Order By: Relevance
“…The specific distribution of ccyA in iACC-forming cyanobacteria, its correlated presence with bicarbonate and calcium transporters, and genetic analyses, all support a pivotal role of ccyA in iACC biomineralization. Further investigations are required to determine whether this function may involve the conserved glutamic acid residues of the C-terminal domain, reminding Glu-rich proteins involved in ACC biomineralization ( Aizenberg et al 2002 ), or the basic amino acids in the N-terminal domain, which may stabilize dense liquid phases of CaCO 3 and delay the formation of ACC ( Finney et al 2020 ). Alternatively, calcyanin may have a more indirect role in iACC biomineralization serving as a cation transporter or a signaling molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The specific distribution of ccyA in iACC-forming cyanobacteria, its correlated presence with bicarbonate and calcium transporters, and genetic analyses, all support a pivotal role of ccyA in iACC biomineralization. Further investigations are required to determine whether this function may involve the conserved glutamic acid residues of the C-terminal domain, reminding Glu-rich proteins involved in ACC biomineralization ( Aizenberg et al 2002 ), or the basic amino acids in the N-terminal domain, which may stabilize dense liquid phases of CaCO 3 and delay the formation of ACC ( Finney et al 2020 ). Alternatively, calcyanin may have a more indirect role in iACC biomineralization serving as a cation transporter or a signaling molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting these results, recent computational studies reported a preference of acidic amino acids for hydrated amorphous calcium carbonate (CaCO 3 ), explaining their involvement in the inhibition of precipitation and stabilization of a liquid phase. 50,86 Further support for our findings comes from the work of Finney et al 86 who compared the effects of amino acids and their oligopeptides (polymer additives: Arg, Asp, and Gly) on CaCO 3 and concluded that (i) the number of solutebinding sites and their accessibility (which requires a certain level of conformational flexibility) to the ionic network plays a crucial role in stabilizing the dense liquid CaCO 3 phase and (ii) the charge distribution of the solutes may control the topology of the CaCO 3 network, which may lead to the inhibition or formation of the mineral.…”
Section: ■ Methodsmentioning
confidence: 99%
“…24,27 An alternative explanation could be the favorable incorporation of bicarbonate into the liquid phase. 28,29 As mentioned above, liquid-liquid phase separation (LLPS) was proven numerous times in case of calcium carbonate, with, but also without additives. 24,[29][30][31] However, liquid precursor phases received minor attention in the discussion of diffusion-based mineralization experiments so far, even if their liquid character is often useful for rationalizing results that are difficult to explain based on classical nucleation mechanisms.…”
Section: Introductionmentioning
confidence: 99%